Advantages and difficulties of ultrasound analysis to determine the fertile period in bitches - Golubev, Oleksandr; Holubyev, O. V.; Holubyev, Oleksandr; Golubev, O. V.; Holubiev, O. V.; Holubyev, Olexander; Holubiev, Olexandr; Голубєв, Олександр Володимирович; Sklyarov, Pavlo; Sklyarov, Pavel; Sklyarov, P. M.; Skliarov, P. M.; et al. (Дніпровський ДАЕУ, 2023)
Definition the fertile period is one of the most important factors contributing to fertilization. Therefore, this analysis is important to solve the problem of infertility. The methods that available today do not provide the expected result, because the vast majority of unsuccessful mating result are related to the incorrect determination of the ovulation period. Therefore, it is important to assess the condition of the ovaries, and the prospect is ultrasound examination, which is an effective method of monitoring the reproductive organs. Ultrasound analysis is a non-invasive and effective method to establish the fertile period in bitches which makes it possible to track changes in the ovaries, detect follicles, their number, and determine the true (morphological) signs of ovulation. Clinical visual and hormonal studies which are based on the indirect determination of the optimal period of female insemination have the advantages in compare with vaginal cytology. Particularly, the use of ultrasound in real time allows to visualize the morphological changes of the ovaries and uterus – the irregular shape of the ovaries with large (0.6-1.2 cm) anechoic structures of a rounded or oval shape with a thin capsule, thickening of the endometrium (up to 0.5-0.8 cm) with a hypoechoic structure of the uterine horns. However, in our research we encountered certain difficulties, which turned out to be the same as other authors. Echography of the ovaries can seem a bit complicated, because the follicles that persist in them have a picture similar to that before and after ovulation. Some ovulated follicles do not always completely collapse (fall) during ovulation and are gradually replaced by luteal tissue while maintaining an echogenic picture on the days of the next ovulation. Non-ovulated follicles can complicate sonography interpretation. To diagnose ovulation, an ultrasound analysis should be performed twice a day, which is inconvenient for the owners. But if the ultrasound test is carried out less often than aforementioned number, there is a risk to miss the moment of ovulation, because the follicles before and after ovulation are very similar. An even more significant problem is the location of the ovaries in bitches – costovertebral angle surrounded by fat and an ovarian sac, which can create technical difficulties. In addition, this diagnostic approach may be more difficult in fat or very large dogs, as well as in dogs with thick skin (Shar Pei, Newfoundland). Визначення фертильного періоду, є одним з найважливіших факторів, що сприяють заплідненню, і отже, має важливе значення у вирішенні проблеми неплідності (малоплідності). Існуючі на сьогодні методи не забезпечують очікуваного результату, бо переважна більшість нерезультативних в’язок пов’язані з неправильною визначенням періоду овуляції. Тому важливе значення має оцінка стану яєчників, а перспективу – ультразвукове дослідження, яке є ефективним методом контролю органів репродуктивної системи. Сонографічне дослідження є неінвазивним і ефективним методом визначення фертильного періоду у сук, що дає можливість відстежити зміни у яєчниках, виявити фолікули, їх кількість і визначати істині (морфологічні) ознаки овуляції. Порівняно з вагінальною цитологією, клініко-візуальним та гормональним дослідженнями, які ґрунтуються на опосередкованому визначенні оптимального часу осіменіння самок, використання ехографії в режимі реального часу дозволяє візуалізувати морфологічні зміни яєчників та матки – неправильна форма яєчників з великими (0,6-1,2 см) анехогенними структурами округлої чи овальної форми з тонкою капсулою, потовщення ендометрію (до 0,5-0,8 см) з гіпоехогенною структурою рогів матки. Однак, в наших дослідженнях ми зіштовхнулися і з певними труднощами, які виявилися тотожними з іншими авторами. Так, ехографія яєчників може видатися дещо складною, бо персистуючі в них фолікули мають картину, схожу з такою до і після овуляції. Деякі овульовані фолікули не завжди повністю колабуються (спадають) під час овуляції і поступово заміщаються лютеїновою тканиною, зберігаючи при цьому ехогенну картину в дні наступної овуляції. Можуть ускладнити інтерпретацію сонографії і неовульовані фолікули. За діагностики овуляції ультразвукове дослідження необхідно проводити двічі на день, що незручно для власників. Але якщо проводити дослідження рідше, можна пропустити момент овуляції, адже фолікули до та після овуляції дуже схожі. Ще більш значною проблемою є розташування яєчників у реберно-хребетному куті у сук, оточених жиром та яєчниковою сумкою, що може створити технічні труднощі. Крім того, дослідження може видатися складнішим у вгодованих собак дуже великого розміру або у тих, які мають товсту шкіру (шарпей, ньюфаундленд).
Переваги та складнощі за використання сонографії для визначення фертильного періоду у сук
Голубєв Олександр Володимирович https://orcid.org/0000-0001-8953-5148 Скляров Павло Миколайович https://orcid.org/0000-0002-4379-9583 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813 Вакулик Вячеслав Володимирович https://orcid.org/0000-0001-8773-2287
Keywords: optimal insemination time; оптимальний час осіменіння; female dog; самки собак; ultrasound analysis; ультразвукове дослідження